2016
DOI: 10.1073/pnas.1612620113
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for dual specificity of yeast N-terminal amidase in the N-end rule pathway

Abstract: The first step of the hierarchically organized Arg/N-end rule pathway of protein degradation is deamidation of the N-terminal glutamine and asparagine residues of substrate proteins to glutamate and aspartate, respectively. These reactions are catalyzed by the N-terminal amidase (Nt-amidase) Nta1 in fungi such as Saccharomyces cerevisiae, and by the glutamine-specific Ntaq1 and asparagine-specific Ntan1 Nt-amidases in mammals. To investigate the dual specificity of yeast Nta1 (yNta1) and the importance of seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 39 publications
1
35
0
1
Order By: Relevance
“…1 and 2 and SI Appendix, Fig. S2A) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Other studies, in the 1990s and afterward, have also identified many internal degrons, defined as degradation signals whose functionally essential elements do not include either Nt-residues or C-terminal (Ct) residues.…”
Section: Terminology For Proteolytic Pathways That Target N-termini Amentioning
confidence: 99%
“…1 and 2 and SI Appendix, Fig. S2A) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Other studies, in the 1990s and afterward, have also identified many internal degrons, defined as degradation signals whose functionally essential elements do not include either Nt-residues or C-terminal (Ct) residues.…”
Section: Terminology For Proteolytic Pathways That Target N-termini Amentioning
confidence: 99%
“…In contrast, N-terminal Asn, Gln, Glu, and Asp (as well as Cys, under some conditions) are destabilizing because of their preliminary modifications, including N Ī± -terminal deamidation (Nt-deamidation) and N Ī± -terminalarginylation (Nt-arginylation) (Fig. 1E) (21, 22, 25, 37). …”
mentioning
confidence: 99%
“…N-terminal Arg, Lys, His, Leu, Phe, Tyr, Trp, Ile, and Met (if Met is followed by a bulky hydrophobic residue) are directly recognized by N-recognins (15,27,32). In contrast, N-terminal Asn, Gln, Glu, and Asp (as well as Cys, under some conditions) are destabilizing because of the enzymatic deamidation of N-terminal Asn and Gln and the arginylation of N-terminal Asp, Glu, and (oxidized) Cys (33)(34)(35)(36)(37).…”
mentioning
confidence: 99%